Evaluation Of Cytokines Changes In Patients Infected With Giardia lamblia In Comparison With Healthy Subjects - Mitra Zarebavani; Nasrin Dashti; Nahid Einollahi; Arezoo Jamali (Tehran University of Medical Sciences, 2012)
Background and Aim: Human Giardisis infection is caused by the flagellate protozoa. Giardia lamblia, which lives in the small intestine, causing damage and may also cause gastrointestinal symptoms. This parasitic disease has a worldwide distribution and prevalence varies from 5% to 30%. The role of both humeral and cellular immune response in the host defense against parasites has proven. Since an immune response is directly affected by cytokine, study of cytokines changes in patients with giardiosis is of particular importance. Materials and Methods: In this study the serum levels of IL-2 - 4 - 6 to 17 and 23 in patients and healthy subjects were measured and compared. Fasting blood samples were taken from the volunteers, ELISA was performed to measure cytokines. Results: In this study, the amount of IL-2 and IL-6 in infected patients was significantly more than the controls, but IL-4 levels were significantly lower in infected individuals (P=0.0001). Also for the first time in people with giardiasis IL-17 and IL-23 was measured and there was a significant aifference in these cytokines between the infected patients healthy controls(respectively P=0.044 and P=0.03) Conclusion: Host defense response against parasitic infections, is directly and affected by cytokines. Increased interleukin 2, 6, 17 and 23 in patients with Giardiosis was probably caused by immune response and local intestinal inflammation.